2017
DOI: 10.1093/annweh/wxx075
|View full text |Cite
|
Sign up to set email alerts
|

First Metagenomic Survey of the Microbial Diversity in Bioaerosols Emitted in Waste Sorting Plants

Abstract: Waste sorting activities are source of occupational bioaerosol exposures that are associated with several health disorders. New analytical tools, based on next-generation sequencing (NGS) technologies, provide powerful methods to assess the microbial composition of bioaerosols. The objectives of the study were (i) to assess the feasibility and the repeatability of NGS-based biodiversity measurements and (ii) to study the microbial biodiversity using NGS in bioaerosols emitted in a waste sorting plant (WSP). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 37 publications
(51 reference statements)
3
48
0
Order By: Relevance
“…Table 1 lists a collection of occupational studies that have employed ITS region sequencing and the fungal taxa most frequently identified. Working environments assessed using this methodological approach have included indoor office buildings [1517], biomethanization plants [18], and biowaste sorting facilities [19, 20••], as well as agricultural commodity and harvesting operations [2123] (Table 1). These studies have utilized either ITS clone library approaches or more recent high-throughput sequencing platforms such as Illumina MiSeq.…”
Section: Occupational Fungal Community Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 lists a collection of occupational studies that have employed ITS region sequencing and the fungal taxa most frequently identified. Working environments assessed using this methodological approach have included indoor office buildings [1517], biomethanization plants [18], and biowaste sorting facilities [19, 20••], as well as agricultural commodity and harvesting operations [2123] (Table 1). These studies have utilized either ITS clone library approaches or more recent high-throughput sequencing platforms such as Illumina MiSeq.…”
Section: Occupational Fungal Community Analysismentioning
confidence: 99%
“…Clinically relevant fungal taxa placed in the order Pleosporales that expresses homologous Alt a 1 allergen [58] were identified in a wheat grain production facility and included Epicoccum nigrum , Alternaria ethzedia , and Didymella exitialis (Table 1) [22]. Sequences placed in the Basidiomycota were also resolved in these occupational environments and included the Agaricomycetes in biomethanization facilities [18], as well as Wallemia species and Cryptococcus victoriae in a waste sorting plant [19] and wheat production facility [22], respectively. Studies of outdoor biowaste and agricultural commodity processing demonstrate the ubiquity of pre-established fungal contaminants such as A. fumigatus but additionally highlight overlooked fungal sources placed in the Ascomycota and Basidiomycota to be more prevalent than previously estimated and contribute to worker exposures.…”
Section: Occupational Fungal Community Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…There are some limitations in this study, including the use of screening media for passive sampling, wherein the number of obtained azole-resistant isolates belonging to the genus Aspergillus may be underestimated due to the dominance of other genera with faster growth rates (Degois et al 2017), such as the isolates belonging to Mucorales order (especially in the waste industry). As Mucorales are, in general, less susceptible to voriconazole, the growth of these species in voriconazole-screening media, may hinder the presence of Aspergillus (Springer et al 2016;Caetano et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Progress in the field has been stimulated by advances in other areas which have been applied to the study of infectious bioaerosols. These include: (a) enhanced detection by molecular methods, principally real-time and quantitative PCR, nextgeneration sequencing, metagenomics, and biosensors (25)(26)(27)(28)(29)(30), and (b) establishment of both conventional and novel infrastructure, such as small and large-scale wind tunnels, biocontained rotating drums for aging aerosols, and field-ready aerosol samplers (31)(32)(33). Ongoing research has also facilitated the development and dissemination of procedures and protocols for experimental work, including artificial aerosols, as well as animal models of transmission including the ferret model for influenza virus transmission and macaque model for Ebola virus transmission (34,35).…”
Section: Value Proposition For the Study Of Potentially Infectious Bimentioning
confidence: 99%